Implementing Innovatory Transport Measures: What Local Authorities in the UK Say About Their Problems and Requirements - Hull, Angela (European Journal of Transport and Infrastructure Research, 2009)
There is a growing emphasis on the need to secure an integrated transport system that both serves the needs of the economy and that contributes to a wider sustainability agenda which includes prudent use of natural resources and equitable access to jobs and facilities. Although the UK government has not set specific targets for emission reduction or accessibility for the transport sector, all local highway authorities in England are now required to set out five year programmes with commitments on progress on four national shared priorities, which include the reduction of polluting emissions from transport and improved public transport. Transport practitioners have a key role to ensure that the foundations are laid now for the transport sector to be in a position to offer an integrated, resource efficient transport system in urban areas. Research has indicated that the principal barriers to achieving more sustainable transport strategies are poor policy integration and coordination, counterproductive institutional roles, unsupportive regulatory frameworks, weaknesses in pricing, poor data quality and quantity, limited public support and lack of political resolve. This paper reports on a study examining the efficacy of the decision support tools available to local transport officers to achieve more sustainable transport options in 16 local authorities in the UK. Results from two questionnaires and a series of follow-up interviews are combined over a four year period to identify where significant support to transport officers is needed. The results suggest that technical and financial support is still necessary in the development, appraisal, monitoring and evaluation of integrated, sustainable, urban travel strategies.